Analisis Strategi Usaha Frozen Food "Omahnong" Dengan 10 Types Of Innovation Dan Business Model Canvas - Safira Fitria; Aries Kurniawan (Journal of Management and Social Sciences, 2023)
The frozen food business continues to experience an increase in transaction value from 2020 to 2022. However, it is different from the Omahnong, which has decreased from 2020 to 2022. In solving the problem, new business innovation is needed. The research aims to find out the business model canvas that will be applied after doing ten types of innovation, the ten types of innovation strategy that has been carried out and the new ten types of innovation strategy. This research uses qualitative research methods with a descriptive approach. The results of the study found nine elements of Omahnong's business model canvas after doing ten types of innovation. In addition, it was found that the ten types of innovation strategies that have been carried out by Omahnong are cost leadership, flexible manufacturing, superior product and community and belonging and the results of the new and appropriate ten types of innovation strategies for Omahnong are cost leadership, predictive analysis, superior product, loyalty program, and process automation. This research can be used as a reference for entrepreneurs in innovating business strategies and can help Omahnong in developing its business.